ARCHITECTURAL PHOTOGRAPHY & THE ESSENCE OF PHOTOGRAPHY - Srivastava, Mihir; Naaz, Shaila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Architectural photography isn’t just about taking pictures of buildings; it’s an art that attempts to capture the real spirit of those structures. This study aims to examine the importance of architectural photography and its role in visualisation of buildings. Architectural photography helps turn 3-dimensional buildings into 2-dimensional pictures that reflect the architects’ mindset as well as have the power to evoke strong emotions in individuals. Photographers use their cameras to play with light, shadows, shapes, and space to reveal the hidden stories within the buildings. Architectural photos do more than just capture what a building looks like; they help individuals to connect with and understand the cultural, social, and historical context of these structures. The objectives of this study were to identify the importance of architectural photography, to gauge individuals’ opinions on architectural photography, to develop a comprehensive view of architectural photography in the Indian context, and to explore the relationship between photography and architecture. This exploration also looks at how architecture and photography work together: emphasizing the reciprocal relationship between the two. To study the same, the authors collected data from different people through a questionnaire, which was analysed using descriptive methods such as the pie chart. The researchers also presented some of their photographs in order to elaborate on their understanding of the role of photography in architecture. The limitations of the current study were noted to be a scarcity of relevant cultural literature on the topic, lack of professional architectural photographers and individual differences in perception of photography.